Cutaneous mucormycosis or black fungus of right shoulder region- rare case report - Gupta, Madhusoodan; Varshney, Deepti (International Surgery Journal, 2021)
Cutaneous mucormycosis or black fungus is a fungal infection which is caused by fungi of class zygomycetes and having high morbidity and mortality. It is an opportunistic infection, which is prevalent in immunocompromised patients. Risk factors associated with mucormycosis are diabetes mellitus, organ transplant, trauma, burn and long-term steroid use. Here author reports a case of mucormycosis of right shoulder complicated with necrotizing fasciitis in a diabetic patient. Patient underwent multiple sittings of radical debridement along with empirical therapy of liposomal Amphotericin B followed by skin grafting.